ASSESSMENT OF NURSING KNOWLEDGE AND ATTITUDES TOWARD PALLIATIVE CARE FOR END-OF-LIFE PATIENTS - ZAFAR , F; RAZA , A; KOUSAR , R (Biological and Clinical Sciences Research Journal, 2024)
Palliative care is an essential component of healthcare for older dying patients, requiring adequate knowledge and positive attitudes from nurses to ensure quality care. Understanding the current level of knowledge and attitudes among nurses can guide interventions to improve care delivery. Objective: To assess the knowledge and attitudes of nurses towards palliative care for older dying patients. Methods: A cross-sectional study was conducted in the Nursing Department of Nishtar Hospital, Multan from September 2023 to September 2024. A total of 100 nurses involved with palliative care of elderly patients were selected for the study. Knowledge of nurses was evaluated by the Palliative Care Quiz for Nursing which contained 20 questions that could be answered by selecting true, false, or unknown options. The attitudes of nurses were assessed on a seven-item thanatophobia scale which could be answered on a Likert scale from 1 to 7 with 1 being strongly agree and 7 being strongly disagree. Results: The mean knowledge score was 12 ± 3.1 which showed a moderate understanding with a score range of 6-19. The median attitude score on the thanatophobia scale was 13 with a score range of 8 to 35. Age (r= -0.347, p=0.006) and experience (r= -0.286) were negatively associated with attitudes and these associations were significant. Total knowledge scores and total attitude scores were moderately and negatively associated indicating that good knowledge was correlated to positive attitudes (p=0.008). Conclusion: A moderate knowledge level and favorable attitudes of nurses were recorded towards palliative care. However, more experience and training can improve these scores.